Brand Coolness in Academic Literature: A Bibliometric Exploration of Global Research Trends and Collaborations - Loso Judijanto (Eastasouth Institute, 2026)
The current study presents a detailed bibliometric examination of the recently evolving concept of brand coolness. The study presents a comprehensive examination of the evolving notion of brand coolness by applying methodologies such as co-authorship analysis, co-citation map analysis, and key word analyses. The study results indicate the growing role of luxury factors, self-brand associations, and sustainability in shaping brand coolness from a consumer perception point of view. The study concludes that the recent brand coolness concepts have attached importance to non-concrete product features. Besides contributing to advancements in brand coolness theories, this study provides a marketer with a detailed insight for integrating brand coolness concepts for unlocking competitive advantages.